Microcrystalline dolomite in a middle Permian volcanic lake: Insights on primary dolomite formation in a non‐evaporitic environment - Jiao, Xin; Liu, Yi‐Qun; Yang, Wan; Li, Hong; Meng, Zi‐Yuan; Zhao, Min‐Ru; Li, Zhe‐Xuan (Sedimentology, 2023)
Lacustrine dolomite nucleation commonly occurs in modern and Neogene evaporitic alkaline lakes. As a result, ancient lacustrine microcrystalline dolomite has been conventionally interpreted to be formed in evaporitic environments. This study, however, suggests a non‐evaporitic origin of dolomite precipitated in a volcanic–hydrothermal lake, where hydrothermal and volcanic processes interacted. The dolomite occurs in lacustrine fine‐grained sedimentary rocks in the middle Permian Lucaogou Formation in the Santanghu intracontinental rift basin, north‐west China. Dolostones are composed mainly of nano‐sized to micron‐sized dolomite with a euhedral to subhedral shape and a low degree of cation ordering, and are interlaminated and intercalated with tuffaceous shale. Non‐dolomite minerals, including quartz, alkaline feldspars, smectite and magnesite mix with the dolomite in various proportions. The 87Sr/86Sr ratios (0.704528 to 0.705372, average = 0.705004) and δ26Mg values (−0.89 to −0.24‰, average = −0.55‰) of dolostones are similar to those of mantle rocks, indicating that the precipitates mainly originated from fluids that migrated upward from the mantle and were subject to water–rock reactions at a great depth. The δ18O values (−3.1 to −22.7‰, average = −14.0‰) of the dolostones indicate hydrothermal influence. The trace and rare earth element concentrations suggest a saline, anoxic and volcanic–hydrothermally‐influenced subaqueous environment. In this subaqueous environment of Lucaogou lake, locally high temperatures and a supply of abundant Mg2+ from a deep source induced by volcanic–hydrothermal activity formed favourable chemical conditions for direct precipitation of primary dolomite. This study's findings deepen the understanding of the origin and processes of lacustrine primary dolomite formation and provide an alternative possibility for environmental interpretations of ancient dolostones.